2003
DOI: 10.4015/s1016237203000134
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of a Dental Implant

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In the case of models B, D, and F, which had four overdenture supports regardless of the types of attachments used, the results showed that higher von Mises stress was observed at the distal sites of the second overdenture‐supporting foundation bilaterally. This observation substantiates those of Hung and Tsai, 27 Nagasao et al, 28 and Meijer et al, 29 which suggested that high stress values are due to the location of the implants nearest to the loading sites that show the highest stress concentrations. In addition, this posteriorly applied load resulted in an increase in stress delivered to the edentulous ridge by the denture base.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of models B, D, and F, which had four overdenture supports regardless of the types of attachments used, the results showed that higher von Mises stress was observed at the distal sites of the second overdenture‐supporting foundation bilaterally. This observation substantiates those of Hung and Tsai, 27 Nagasao et al, 28 and Meijer et al, 29 which suggested that high stress values are due to the location of the implants nearest to the loading sites that show the highest stress concentrations. In addition, this posteriorly applied load resulted in an increase in stress delivered to the edentulous ridge by the denture base.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study confirm the conclusions of many authors that highest bone stresses occur in the cortical bone near the neck of the implant. Huang reported stresses in the cortical bone to be 9.5 times higher than in trabecular bone [20]. This study determined this ratio to be 7.5.…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, however implant diameter increases reduce the stresses. [ 5 ] Further studies are needed with larger samples size to validate the results.…”
Section: Discussionmentioning
confidence: 99%